ESSENCE, FEATURES AND PROSPECTS OF HOUSEHOLD LAND USE IN UZBEKISTAN - Abdullo Ashurov; Shokhrukh Kholdorov; Bahrom Shafkarov (TADQIQOTLAR, 2025)
Abstract. The socio-economic role of homestead land plots and private farms is studied, definitions of their terms are given, the role of the homestead land Fund in ensuring food security of the country and increasing the export potential of fruit and vegetable products is considered. The reasons for the higher efficiency of growing agricultural products in private farms in comparison with other forms of farming, as well as the features of the use of homestead land plots, are studied.